Evaluation of radiometric standards of major building materials used in dwellings of South-Western Nigeria - Aladeniyi, K.; Arogunjo, A.M.; Pereira, A.J.S.C.; Khandaker, Mayeen Uddin *; Bradley, D.A. *; Sulieman, A. (Elsevier, 2021)
Realizing the probable health risk via the exposures to gamma radiations caused by terrestrial radionuclides, concentrations of 40K, 226Ra(238U) and 232Th radionuclides in popularly used building materials were investigated by gamma-ray spectroscopy. A total of 173 samples representative of major building materials (both structural and decorative category) used for Nigerian dwellings were studied. The mean (GM) activity concentrations of the 40K, 226Ra(238U) and 232Th in the surveyed samples are 286 ± 3, 29 ± 3 and 26 ± 5 Bqkg-1 respectively. Associated radiation hazard parameters were estimated and the results are compared with the available literature data and the prescribed limits set by international regulatory bodies to identify the radiometric standards of the studied materials. This study shows that the use of tile and granite should be minimized for building constructions. Moreover, perpetual monitoring of radiation level in clay- and mud-bricks should be intensified to avoid unwanted radiation exposure to dwellers. Overall, measured data may serve as an important component of the database to set up guidelines required for controlling building materials usage in dwelling purposes.